Kesantunan Berbahasa Antara Pedagang dan Pembeli di Pasar Tamanroya Kabupaten Jeneponto - Irma Nirwana; Asia M.; Andi Fatimah (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract: Politeness in Language Between Traders and Buyers at Tamanroya Market, Jeneponto Regency. The purpose of this study is to describe the politeness principles and politeness violations in Makassar language in the interaction of traders and buyers at Tamanroya Market, Jeneponto Regency. This type of research ia a qualitative descriptive research. The method upsed in collectiong research data is recording, free viewing, and recording. The data analysis method in this study begins with describing the data in the form of recorded conversation data in the field, the next process is identifying the data, and reducing words. The validity of the data was obtained from the triangulation process using the technique of triangulation of data sources, observers and theories. The results of this study are as follows. (1) the politeness principle consists of the maxim of wisdom and agreement, the maxim of generosity, the maxim of humility, the maxim of praise, the maksim of agreement and the maxim of sympathy. (2) violation of politeness maxims in the form of (a) violation of two maxims, namely the maxim of wisdom and maxim of agreement (b) violation of three maxims, namely the maxim of wisdom, the maxims sympathy, and the maxim of agreement.Keywords: politeness in language, politeness principles, violation of maxims, traders and buyers